(untitled) (University of Khartoum Engineering Journal, 2022)
Proper Orthogonal Decomposition (POD) eigenfunctions have many useful applications in the analysis of turbulent shear flows, e.g., reconstruction of flow statistics, investigation of coherent structures, basis for low dimensional modelling (LDM), and flow control. The major shortcoming of POD method and its implementation to LDM and flow control is the dependence of POD basis on the flow parameters and geometry from which they were extracted. The paper develops a proposal for a model of energetic-structures in which the cross-spectral tensor is determined from the solution of spectral equations. The obtained energetic-structures are similar to those observed in experiments or extracted from numerical simulations data.